Role and Significance of Circulating Biomarkers: miRNA and E2F1 mRNA Expression and Their Association with Type-2 Diabetic Complications - Mirza Masroor Ali Beg; Amit Kumar Verma; Mohd Saleem; Fayez Saud Alreshidi; Fahaad Alenazi; Hafiz Ahmad; Prakash C. Joshi (International Journal of Endocrinology)
Background. Type 2 diabetes mellitus (T2DM) has emerged as an epidemic affecting more than four hundred million people throughout the world. It is a multifactorial disease with range of environmental and genetic factors responsible for its prevalence. In search of novel biomarkers for recording progress of various metabolic diseases, small noncoding RNA in general and microRNAs (miRNAs) in particular have emerged as the most promising biomarkers for diagnosing variety of diseases including diabetes. An increasing number of studies have been published, reporting the quantification of miRNAs in blood of subjects with diabetes and mostly aimed at identifying miRNA modulation in chronic diabetic complications. Due to its association with immune system homeostasis and potential capability to predict diabetes development, the profile of circulating miRNAs may also provide useful information about diabetes pathogenic mechanisms. Thus, the present study aimed to understand the role and expression of microRNA330 and E2F1 mRNA expression in patients with T2DM. Methodology. The present study includes a total of 200 individuals: 100 “individuals with T2DM referred to as “cases” and 100 healthy individuals referred to as “controls”. Extracted RNA was used to synthesise the cDNA for microRNA-330 and E2F1 mRNA expression. Taqman assay method has been used to analyse the microRNA-330 expression in the cases and controls and SYBR green dye was used to study the E2F1 mRNA expression. Results. Statistically significant difference was observed in all the selected 5 biochemical parameters among T2DM cases and healthy controls. Risk factors like hypertension were observed to be significantly associated with reduced HDL (p=0.01), increased TG (p=0.0008), and cholesterol (p<0.0001) in hypertensive T2DM cases as compared to nonhypertensive T2DM cases. Obese patients showed significant increase in TG (p=0.01) and cholesterol (p<0.0001) as compared to nonobese patients. Similarly, increased TG (p=0.001) and cholesterol (p<0.0001) was observed in the case of alcoholic patients as compared to nonalcoholic patients. Also, patients with smoking habit showed increased TG (p=0.009p = 0.009), cholesterol (p<0.0001), and VLDL (p=0.01) as compared to nonsmokers and differences among them was found to be statistically significant. Besides this, significant impact of risk factors like hypertension, obesity, alcoholism, and smoking were observed on microRNA-330 expression and E2F1 mRNA expression. A 7.72-fold increased microRNA-330 and 0.05-fold decreased E2F1 mRNA expression was observed among T2DM cases as compared to healthy controls. Increased expression of microRNA-330 was observed in hypertensive cases (9.61-fold, p<0.0001), obese cases (9.33-fold, p=0.0008, alcoholic cases (9.07-fold, p<0.0001), and smoking cases (8.41-fold, p=0.01) as compared to nonhypertensive, nonobese nonalcoholic, and nonsmoking cases, and differences among them were found to be significant. Decreased expression of E2F1 mRNA expression was observed in patients with alcoholism (0.03-fold, p=0.002) and smoking (0.03fold, p<0.0001) while patients who were nonalcoholic and nonsmokers showed 0.07-fold increase in expression, and differences among them were found to be statistically significant. Conclusion. The present study demonstrated that increased level of microRNA-330 and decreased level of E2F1 mRNA expression were found to be associated with pathogenesis of T2DM patients. Risk factors such as hypertension, obesity, alcoholism, and smoking may be were found to be associated with microRNA-330 and E2F1 mRNA expressions, and it can prove a reliable biomarker for T2DM disease progression could be linked to chronic diabetic complications.